CEGAH AMPUTASI DENGAN PENATALAKSANAAN DIABETES MELITUS DI MASA PANDEMI COVID-19 - Fitria Alisa; Vivi Syofia Sapardi; Lola Despitasari; Muhammad Farid; Alex Contesa (JURNAL ABDI MERCUSUAR, 2021)
Background : Diabetes mellitus (DM) is an insulin insufficiency disorder caused by disruption of insulin products by Langerhans beta cells or the body's cells are less responsive to insulin. Covid-19 attacks all ages, especially those who have chronic diseases (co-morbid) have a more frequent risk of getting it with bad complications from this disease. Physical exercise (Diabetes leg exercises) is one of the pillars in the management of DM, which functions to improve insulin sensitivity and maintain body fitness during the COVID-19 pandemic. The goal of this community service is to prevent amputation by managing diabetes mellitus. Method : This community service method refers to action research with the formation of a DM prolanis group at the MERCUBAKTIJAYA clinic in Padang, socialization and education related to the management of diabetes mellitus, as well as monitoring and evaluation that have been carried out in collaboration with the MERCUBAKTIJAYA clinic in Padang as a follow-up to this activity. Result: 90% of the participants were enthusiastic about the activity and were able to re-practice the material presented.